STATUS HARTA BERSAMA MENURUT PERSPEKTIF UNDANG-UNDANG NO 1 TAHUN 1974 DAN HUKUM ISLAM - ., Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
Field of this research is let?s to know about Harta Bersama In Islamic law. The method of this research is description of analysis. By This article, we are know that human being was create a marriage institution for a long long time ago. Every marriage institution need a capital. The line of Islamic family is patrilineal. By this line of family, the capital of Islamic familly only from a husband. Actually, we met a harta bersama in Islamic society. The existence of harta bersama have a judge from Islamic law. We thruth that legitimation of harta bersama by Islamic law by the rule ? al-aadah muhakkamah ? not contrary by syariah.